PENGARUH MEKANISME CORPORATE GOVERNANCE, PERGANTIAN AUDITOR, SPESIALISASI INDUSTRI AUDITOR, DAN UKURAN KAP TERHADAP INTEGRITAS LAPORAN KEUANGAN (Studi pada Perusahaan Manufaktur yang Terdaftar di Bu - Rona Tridiyanto (AKT 15 UMY 125, 2015)
*125 The researchers aimed to examine the influence of corporate mechanism gonernance, change of auditors, auditor industry-specialization, and the size of the firm on the integrity of the financial statements. The sample in this study were 136 companies that against in Indonesia Stock Exchange (IDX) for 3 consecutive years from 2011-2013 as the sample is based on purposive sampling method. The data used in this study is a secondary form of financial statements of manufacturing companies, and other references that support this research. Data analysis techniques using classical assumption: normality test, multicollinearity, autocorrelation, and heteroscedasticity test. Test this hypothesis using multiple regression analysis. These results indicate that: independent commissioners negatively affect the integrity of the financial statements, the audit committee a positive effect on the integrity of the financial statements, ownership institutionally positive effect on the integrity of the financial statements, managerial ownership adversely affected the integrity of the financial statements, the auditor turn negatively affect the integrity of the financial statements , auditor industry specialization negatively affect the integrity of the financial statements and the size of the firm negatively affect the integrity of the financial statements.